2020
DOI: 10.7759/cureus.10825
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Outcomes of Complementary and Alternative Medicine Use Among Adult Patients With Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease that causes demyelination of the central nervous system. No treatment has been shown to be curative; thus, we assume that the tendency for patients with MS to use unconventional therapies, such as complementary and alternative medicine (CAM), might increase. The aim of this study was to explore the pattern of CAM use among patients with MS at a tertiary health care center in Saudi Arabia (SA). This was a questionnaire-based observational cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Of great importance are also cultural disparities that strongly influence social acceptance and attitudes towards CAM, but also have an influence on the type of CAM used in different parts of the world. For example, a recently published study from Saudi Arabia [15] has demonstrated that the most commonly used modalities are prayer or reciting the Koran, while in other regions of the world, such as Europe, more popular are vitamins, massage or yoga [5,10,16]. According to our analysis, the most frequently used methods were vitamins (48%), and psychophysical methods such as massage or relaxation techniques (44%), which is similar to other European countries [5,17].…”
Section: Discussionsupporting
confidence: 58%
“…Of great importance are also cultural disparities that strongly influence social acceptance and attitudes towards CAM, but also have an influence on the type of CAM used in different parts of the world. For example, a recently published study from Saudi Arabia [15] has demonstrated that the most commonly used modalities are prayer or reciting the Koran, while in other regions of the world, such as Europe, more popular are vitamins, massage or yoga [5,10,16]. According to our analysis, the most frequently used methods were vitamins (48%), and psychophysical methods such as massage or relaxation techniques (44%), which is similar to other European countries [5,17].…”
Section: Discussionsupporting
confidence: 58%
“…The characteristics of itching common to these reported cases include abrupt onset and end of the episodes ranging from several seconds to several minutes with a frequency of 5-6 times a day or more mostly including the face, trunk, and extremities and rarely lower extremities [9]. The case described here presented with symptoms similar to those described by the aforementioned reports.…”
Section: Discussionsupporting
confidence: 74%
“…A national survey on 28,625 adult Americans found that those with diabetes were significantly more likely to use prayer, which was defined as whether they had ever prayed specifically for their own health [ 29 ]. Another recent study on patients with multiple sclerosis also showed that prayer was the most frequently used complementary therapy modality [ 30 ]. In Taiwan, a cross-sectional study of female patients with breast cancer receiving anticancer therapy reported a prevalence of 46.4% in the use of spiritual healing, especially prayer, since receiving a diagnosis of breast cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%